(untitled) (Alberta Journal of Educational Research, 2015)
The need for and lack of integration of theory and practice in initial teacher education programs has been discussed as a central issue for teacher education. This article reports on a study that surveyed university-based teacher educators in Atlantic Canada on their perspectives regarding how theory and practice can be integrated, how they and the programs they work in integrate theory and practice, and what challenges they perceive for the integration of theory and practice in their own teaching and the teacher education programs within which they work. Un enjeu central qui ressort des discussions sur la formation des enseignants est le besoin d’intégrer la théorie et la pratique dans les programmes de formation initiale. Cet article rend compte d’une étude impliquant une enquête auprès de formateurs universitaires d’enseignants dans le Canada atlantique pour connaitre leur points de vue sur les façons d’intégrer la théorie et la pratique, et sur les défis qu’ils perçoivent pour l’intégration de la théorie et la pratique dans leur propre enseignement et dans les programmes de formation des enseignants au sein desquels ils travaillent.